On income, democracy, political stability, and internal armed conflicts - Shiva, M; Molana, H (University of South Florida, 2022)
Whether or not a country is likely to encounter an internal armed conflict is considered in the literature to depend, among other things, on its extent of economic and political development. Using a dataset covering 139 countries over the 1961-2011 period, we find that a country’s per capita income has an unambiguously negative effect on the probability that it encounters an armed conflict as long as it does not suffer from a severe political instability. In contrast, countries that experience severe political instability are more likely to encounter an armed conflict the higher is their per capita income. The policy implication of our result is clear: safeguarding political stability during hard times is essential – and should take precedence over enhancing democracy and economic growth – for reducing the risk of internal armed conflicts. Our findings do not undermine the importance of protecting democratic institution or accountability, but underscore the importance of collaboration across opposing parties to progress while preserving the political stability